Harnessing the Neural Stem Cell Secretome for Regenerative Neuroimmunology - Willis, Cory M.; Nicaise, Alexandra M.; Hamel, Regan; Pappa, Vasiliki; Peruzzotti-Jametti, Luca; Pluchino, Stefano (Frontiers in Cellular Neuroscience, 2020)
Increasing evidence foresees the secretome of neural stem cell (NSCs) to confer superimposable beneficial properties as exogenous NSC transplants in experimental treatments of traumas and diseases of the central nervous system (CNS). Naturally produced secretome biologics include membrane-free signalling molecules and extracellular membrane vesicles (EVs) capable of regulating broad functional responses. The development of high-throughput screening pipelines for the identification and validation of NSC secretome targets is still in early development. Encouraging results from pre-clinical animal models of disease have highlighted secretome-based (acellular) therapeutics as providing significant improvements in biochemical and behavioural measurements. Most of these responses are being hypothesised to be the result of modulating and promoting the restoration of key inflammatory and regenerative programs in the CNS. Here we will review the most recent findings regarding the identification of NSC-secreted factors capable of modulating the immune response to promote the regeneration of the CNS in animal models of CNS trauma and inflammatory disease, and discuss the increased interest to refine the pro-regenerative features of the NSC secretome into a clinically available therapy in the emerging field of Regenerative Neuroimmunology.